Needs for Consultancy of Vietnam high school students: A case study - LE THI QUYNH, NGA; NGUYEN HUU, CHAU (Archives of Business Research, 2020)
This paper investigates the needs for consultancy of Vietnam high school students in resolving obstacles encountered in their academic and daily lives. Data are collected from a survey on 253 teachers and 1,089 students of 6 high schools in the urban and suburban areas (represented by Hanoi, Hochiminh City, and Thanh Hoa province) in the Northern, Southern and Central Region. It has been found that students face a range of difficulties on a regular basis and to different degrees. As such, they adopt certain solutions to specific issues. In this paper, teachers' consultancy is studied in order to figure out whether it is an option favored by students, and what they expect from teachers ‘advice. Results show that although teachers are not hard to be reached, students rarely seek their advice since they hold higher expectations for consultancy than what their teachers can offer.